Novel low bandgap phenothiazine functionalized DPP derivatives prepared by direct heteroarylation: Application in bulk heterojunction organic solar cells. (June 2017) - Maglione, Cira; Carella, Antonio; Centore, Roberto; Chávez, Patricia; Lévêque, Patrick; Fall, Sadiara; Leclerc, Nicolas
Abstract: The synthesis by direct heteroarylation of three novel low bandgap donor-acceptor-donor molecules is reported herein. The molecules are based on three different diketopyrrolo-pyrrole (DPP) electron deficient cores, functionalized with different electron rich heteroarenes, (thiophene, thiazole and thienothiophene) and symmetrically linked to two terminal donor phenothiazine rings. The optical properties of the synthesized dyes have been measured both in solution and as thin film and a focus has been given on the study of optoelectronic properties as a function of the different heteroarenes (thiophene, thiazole or thienothiophene) functionalizing the DPP core. Bandgap values as small as 1.55 eV have been observed. The energy of the Frontier orbitals has been estimated by means of electrochemical characterization. The electronic properties of the reported molecules have been investigated more in details by computational analysis performed at the DFT level. The new dyes were used as donor materials in BHJ solar cells and the photovoltaic characterization of these devices led to a maximum power conversion efficiency of 0.7%. Graphical abstract: Highlights: Synthesis of low bandgap small molecules by direct heteroarylation. The dyes are based on diketopyrrolopyrrole core and end-capped with phenothiazine. Optical and electrochemical characterization along with computational investigation. Fabrication of solar cells based on the reported dyes with efficiency up to 0.7%.